The Influence of Gamification on Purchase Decisions on the Shopee Platform: A Case Study of Shopee Games Users in West Java - Ahmad Takholi, Roihan; Cahyani, Leni; Junipriansa, Donni (Journal Research of Social Science, Economics, and Management, 2026)
Gamification has become an important digital marketing strategy for creating a more engaging online shopping experience. Shopee implements this strategy through Shopee Games, which allows users to participate in various game activities and earn rewards that can be redeemed during shopping. The present study investigates how gamification applied through Shopee Games influences the purchase decisions of Shopee users in West Java. This research adopted a quantitative approach using descriptive and verificative methods. Data were collected through an online questionnaire completed by 100 respondents who met the predetermined research criteria and were subsequently analysed using descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression, the t-test, and the coefficient of determination with IBM SPSS Statistics. The results show that participants generally reported positive perceptions of the gamification features provided by Shopee Games. Statistical analysis revealed a statistically significant positive relationship between gamification and purchase decisions (? = 0.382; t = 13.162; p < 0.001). Furthermore, gamification accounted for 63.9% of the variance in purchase decisions (R² = 0.639). Overall, the findings suggest that gamification can serve not only as an entertainment feature but also as an effective digital marketing strategy for encouraging consumers' purchase decisions on the Shopee platform.